INOVASI ALAT PERAGA FALAK DALAM PENGUKURAN ARAH KIBLAT (Studi Analisis "Mutsalatsah Qiblah" Menggunakan Bayangan Matahari Setiap Saat) - Al-Anshary, Ahmad Fuad (ELFALAKY: Jurnal Ilmu Falak, 2022)
Qibla direction is the closest direction to the Kaaba. Measuring the Qibla direction is important in society. The problem of Qibla direction is not only a matter of worship, but also related to social problems and community habits. Allah has created the sun as the source of human life. In connection with determining the direction of Qibla, the sun becomes an accurate Qibla direction. Humans wherever they are, as long as they can see sunlight, they can actually determine the direction of Qibla. There are several ways to determine the Qibla direction, ranging from simple to complex. With a simple and low-cost method, it is hoped that it can be an alternative in determining the exact direction of Qibla. With the innovation of the Mutsalatsah Qiblah tool, it is hoped that it will be able to answer the challenges of life that are growing day by day. For this reason, Mutsalatsah Qiblah answers this need, with a simple tool and embedded several other supporting components, which are expected to have the same accuracy as manufactured products such as digital theodolites which have high accuracy.